Adaptations for stealth in the wing-like flippers of a large ichthyosaur - Johan Lindgren; Dean R. Lomax; Robert-Zoltán Szász; Miguel Marx; Johan Revstedt; Georg Göltz; Sven Sachs; Randolph G. De La Garza; Miriam Heingård; Martin Jarenmark; Kristina Ydström; Peter Sjövall; et al. (Nature, 2025)
Abstract With their superficially shark-like appearance, the Mesozoic ichthyosaurs provide a classic illustration of major morphological adaptations in an ancestrally terrestrial tetrapod lineage following the invasion of marine habitats1–3. Much of what is known about ichthyosaur soft tissues derives from specimens with body outlines4–6. However, despite offering insights into aspects of biology that are otherwise difficult to envisage from skeletal evidence alone (such as the presence of a crescentic fluke), information on their soft parts has hitherto been limited to a taxonomically narrow sample of small- to dolphin-sized animals2,4–6. Here we report the discovery of a metre-long front flipper of the large-bodied Jurassic ichthyosaur Temnodontosaurus, including unique details of its soft-tissue anatomy. In addition to revealing a wing-like planform, the fossil preserves a serrated trailing edge that is reinforced by novel cartilaginous integumental elements, herein denominated chondroderms. We also document chordwise-parallel skin ornamentations and a protracted fleshy distal tip that presumably acted like a flexible winglet in life. By integrating morphological and numerical data, we show that the observed features probably provided hydroacoustic benefits, and conclude that the visually guided7,8 Temnodontosaurus relied on stealth while hunting in dim-lit pelagic environments. This unexpected combination of control surface modifications represents a previously unrecognized mode of concealment, and underscores the importance of soft-tissue fossils when inferring aspects of palaeoethology and predator–prey palaeoecology.